Body Weight Changes in Hyperthyroidism: Timing and Possible Explanations during a One Year Repeated Measurement Study. Issue 3 (2nd June 2021) - Karmisholt, Jesper; Carlé, Allan; Andersen, Stig
Abstract : Background: Weight gain during treatment of hyperthyroidism is a frequent and for many patients unwanted outcome. With this repeated measurement study, we explored the timing of weight changes during the first year of antithyroid drug (ATD) treatment and assessed the correlation between body weight changes and changes in thyroid hormones, resting energy expenditure (REE), physical activity level, and energy efficiency. Methods: Patients with new onset hyperthyroidism were investigated every second month during the first year of ATD treatment. At each investigation, the following were measured: body weight, thyroid hormone concentrations, physical activity level, and daily number of steps, REE, and exercise performance. Results: Two men and eleven women, all sedentary, mean age 49(SD: 9.3) years were included. Significant changes after 1 year occurred for body weight (68.9–74.1 kg), thyroid hormones (free T3 [fT3] 17.5 to 4.42 pmol/L), REE (1, 630–1, 484 kcal/24 h), and energy efficiency at lower (50 W) workloads (16.0–17.6%). In individual patients, only REE and fT3 correlated to changes in body weight. Physical activity level did not change during treatment. Conclusion: In this study, treatment of hyperthyroidism was associated with marked increase in body weight in the patients. This increase correlated to a decrease in REE and only to a negligible extent to changes in energy efficiency and not at all to changes in physical activity level of daily living.